Macroeconomic conditions and stock returns in Indonesia’s consumer sector: Evidence of sectoral heterogeneity and financial vulnerability - Chairani Manasye Riama Sinaga; Rahmat Aryo Baskoro (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: This study examines the impact of macroeconomic conditions on stock returns in Indonesia’s consumer sector, with the objective of determining whether these effects differ across sectoral classifications and firms’ financial conditions. Although existing research broadly recognizes the linkage between macroeconomic indicators and stock returns, much of the literature implicitly assumes homogeneous responses across firms and sectors, particularly within the consumer industry. Methods: Using a quantitative panel data approach, this study analyzes firms in the consumer sector listed on the Indonesia Stock Exchange over the 2015–2024 period, incorporating inflation, policy interest rates, exchange rate growth, money supply (M2), unemployment, and real gross domestic product growth as explanatory variables, while controlling for profitability and leverage. Findings: The analysis employs the Common Effects Model with Panel-Corrected Standard Errors to account for heteroskedasticity and cross-sectional dependence, and introduces sector classification and financial distress, measured by the Altman Z-Score, as moderating variables. The results indicate that the influence of macroeconomic factors on stock returns is heterogeneous rather than uniform: policy interest rates consistently exert a negative and statistically significant effect, whereas the effects of inflation, exchange rate movements, money supply, unemployment, and economic growth vary across sectoral classifications and financial distress conditions, as reflected in several significant interaction terms. Conclusion: These findings imply that aggregate macroeconomic signals are transmitted to stock returns through distinct channels depending on firms’ sectoral positioning and financial health. The study therefore concludes that analyses which overlook such heterogeneity risk producing incomplete or misleading inferences regarding macro–return relationships in emerging markets. Novelty/Originality of this article: The novelty of this research lies in its integrated moderation framework, which simultaneously considers sector classification and financial distress within a unified panel setting, thereby offering a more nuanced and context-specific understanding of how macroeconomic factors shape stock returns in Indonesia’s consumer sector.